2002
DOI: 10.1016/s0169-5983(02)00036-9
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum dust ignition behind reflected shock wave: two-dimensional simulations

Abstract: In this paper results of parallel computer simulations on aluminum dust ignition behind a re ected shock wave are presented. Computations show the time-evolution of a complicated ow ÿeld created due to a shock wave collision with a pile of dust, shock re ection from a wall, and its interaction with vortices. Particles, blown away by the incident shock, are heated mainly behind the re ected shock wave. The estimated ignition delay time is of the order of 80 -100 s and is a strong function of the incident shock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 24 publications
1
16
1
Order By: Relevance
“…While some studies suggested that it was a fixed value around the melting temperature of the aluminum particles [21,24], many others suggest that the ignition temperature is not a material property but depends upon the environmental variables, such as the heating rates [25][26][27], particle size [28], specific experimental conditions or methods employed [29,30] and instruments used [29,31,32]. It is still debatable if the ignition of aluminum nanoparticles occurred before or after the melting temperature of aluminum.…”
Section: Influence Of the Heating Ratementioning
confidence: 99%
“…While some studies suggested that it was a fixed value around the melting temperature of the aluminum particles [21,24], many others suggest that the ignition temperature is not a material property but depends upon the environmental variables, such as the heating rates [25][26][27], particle size [28], specific experimental conditions or methods employed [29,30] and instruments used [29,31,32]. It is still debatable if the ignition of aluminum nanoparticles occurred before or after the melting temperature of aluminum.…”
Section: Influence Of the Heating Ratementioning
confidence: 99%
“…Many compressible granular multiphase flows are modelled using the 'dust-gas approximation', which neglects particle-particle interactions and collision processes, and so it effectively assumes that the particles are dilute in the background gas (Collins et al 1994;Benkiewicz & Hayashi 2002;Saito, Marumoto & Takayama 2003;Pelanti & LeVeque 2006;Fedorov, Kharlamova & Khmel' 2007;Kuhl, Bell & Beckner 2010). These models have been used to study detonations of particle suspensions, explosion suppression from aerosolized particles, lifting of dilute dust layers, and the dispersion and combustion of aluminium particles in the turbulent flow field generated by an explosion.…”
Section: Introductionmentioning
confidence: 99%
“…Control and characterization of shock induced ignition processes include ignition of condensed phase explosives [1,2], abnormal ignition of propellants [3], burning of metal additives in rocket motors [4], explosion safety issues in dusty environments (e.g. flour mills, grain elevators and coal mines) [5,6], and the fundamental issues of deflagration-to-detonation-transition (DDT) for single-phase [7] and two-phase mixtures [8].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have employed dusty gas approximations to examine the interaction of shocks. Examples include shocks interacting with inert [9], coal [10], aluminum [4], and hydrocarbon [11] particles and droplets. A recent review of the literature in this area applied to DDT is provided by Zhang [12].…”
Section: Introductionmentioning
confidence: 99%